Tanggung Jawab Direksi (Pengurus) Badan Usaha Milik Negara Dengan Menggunakan Asas-Asas Business Judgement Rule Dalam Pertanggungjawaban Pidana - Sutanto, Sutanto (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
State-Owned Enterprises (SOEs) are a form of business entity or legal entity established by the government to realise the welfare of the Indonesian people in accordance with the mandate of the 1945 Constitution. In the management and implementation of their business activities, SOEs in the form of limited liability companies have their own unique characteristics when compared to private limited liability companies, because these SOEs are also regulated separately by Law No. 19 of 2003 concerning State-Owned Enterprises, in addition to being regulated by Law No. 40 of 2007 concerning Limited Liability Companies. The background and considerations for the enactment of Law No. 19 of 2003 on State-Owned Enterprises include the fact that SOEs are one of the economic actors in the national economy based on economic democracy, playing an important role in the management of the national economy to achieve public welfare, whereas the implementation of the role of SOEs in the national economy to achieve public welfare has not been optimal. Therefore, management and supervision must be carried out professionally. In the management and supervision of SOEs, many directors (managers) of SOEs have been involved in special criminal cases due to errors or negligence in implementing the Business Judgment Rule. Moreover, currently there are not many references or jurisprudence that can save SOE directors if they are suspected of corruption, including the condition of government regulations that do not specifically regulate the application of the Business Judgment Rule.